Impedance based detection of delamination in composite structures - Djemana, Mohamed; Hrairi, Meftah (IOP Publishing, 2017)
Nowadays commercial and military aircrafts are increasingly using composite materials to take advantage of their excellent specific strength and stiffness properties but impacts on composites due to bird-strike, hail-storm cause barely visible impact damage (BVID) that underscores the need for robust structural health monitoring methods. Hence, damage identification in composite materials is a widely researched area that has to deal with problems coming from the anisotropic nature of composites and the fact that much of the damage occurs beneath the top surface of the laminate. This paper focuses on understanding self-sensing piezoelectric wafer active sensors (PWAS) to conduct electromechanical impedance (EMI) in glass fibre reinforced polymer composite to perform structural health monitoring. With the aid of a 3D ANSYS finite element model, an analysis of different techniques for the detection of position and size of a delamination in a composite structure using piezoelectric patches had been performed. The real part of the impedance is used because it is known to be more reactive to damage or changes in the structure’s integrity and less sensitive to ambient temperature changes compared to the imaginary part. Comparison with experimental results is presented to validate the FE results. The experimental setup utilizes as its main apparatus an impedance analyser HP4194 that reads the in-situ EMI of PWAS bonded to the monitored composite structure. A good match between experimental and numerical results has been observed for low and high frequencies. The analysis in this paper provides necessary basis for delamination detection in composite structures using EMI technique.